2009
DOI: 10.1093/ndt/gfp255
|View full text |Cite
|
Sign up to set email alerts
|

The inaccuracy of cystatin C and creatinine-based equations in predicting GFR in orthotopic liver transplant recipients

Abstract: Therefore, the degree of inaccuracy in cystatin C- and creatinine-based predictive equations brings into question their clinical utility in OLT recipients. We have no evidence that cystatin C is superior to creatinine in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2011
2011
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 29 publications
1
13
0
3
Order By: Relevance
“…Some studies have shown that cystatin C may be a better assay for GFR estimation in the setting of cirrhosis [22] and a 2006 study showed that serum cystatin C correlated better with iohexol-based GFR estimates than serum creatinine did [23]. However, a subsequent study in 2009 did not demonstrate improved diagnostic accuracy of cystatin C over serum creatinine in the setting of liver transplantation [24]. Serum cystatin C has been shown to be superior to creatinine as a marker of kidney function in chronic kidney disease [25].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that cystatin C may be a better assay for GFR estimation in the setting of cirrhosis [22] and a 2006 study showed that serum cystatin C correlated better with iohexol-based GFR estimates than serum creatinine did [23]. However, a subsequent study in 2009 did not demonstrate improved diagnostic accuracy of cystatin C over serum creatinine in the setting of liver transplantation [24]. Serum cystatin C has been shown to be superior to creatinine as a marker of kidney function in chronic kidney disease [25].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we performed the IC test to accurately measure renal function of the included patients. SCr‐based equations have been proven to overestimate GFR in patients after OLT [11,14,18,21,32,34]. CysC is not influenced by many of the factors that usually affect sCr in OLT recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Ha 51 Cr-EDTAval mért GFR-rel történt az összehasonlítás, egyes tanulmányok szerint a cisztatin-C-vel meghatározott eGFR volt a valósabb, míg mások szerint a CKDEPIképlet használatával a kreatininnel [21,22,23]. Volt olyan közlemény, amely szerint májtranszplantált betegcsoportban nem volt különbség köztük [24]. Volt olyan, ami szerint ADPKD-ben szenvedő betegek kapcsán együttes mérésük adta a legjobb eredményt [25].…”
Section: Megbeszélésunclassified